2007
DOI: 10.1037/0278-6133.26.6.794
|View full text |Cite
|
Sign up to set email alerts
|

Active and passive distraction using a head-mounted display helmet: Effects on cold pressor pain in children.

Abstract: Although both distraction conditions were effective, the interactive distraction condition was significantly more effective. Implications for the treatment of children's distress during painful medical procedures are discussed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
141
5
6

Year Published

2011
2011
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 160 publications
(165 citation statements)
references
References 46 publications
11
141
5
6
Order By: Relevance
“…The HMD allows both occlusion of the external environment and, audiovisual immersion that is superior to immersion with only a single sense modality (Wismeijer & Vingerhoets, 2005). Recently, researchers have begun to refine the comparisons between different VR paradigms and have discovered that interactive environments are better than passive ones (Dahlquist, et al, 2007) and that higher quality virtual reality environments are better than lower quality ones (H. G. Hoffman, et al, 2006;H. G. Hoffman, et al, 2004).…”
Section: Interactive Gamingmentioning
confidence: 99%
“…The HMD allows both occlusion of the external environment and, audiovisual immersion that is superior to immersion with only a single sense modality (Wismeijer & Vingerhoets, 2005). Recently, researchers have begun to refine the comparisons between different VR paradigms and have discovered that interactive environments are better than passive ones (Dahlquist, et al, 2007) and that higher quality virtual reality environments are better than lower quality ones (H. G. Hoffman, et al, 2006;H. G. Hoffman, et al, 2004).…”
Section: Interactive Gamingmentioning
confidence: 99%
“…Laboratory studies have explored the relationship between the immersiveness of the VR system and the magnitude of pain reduction during VR distraction. 11,[14][15][16][17] These studies have 16 and use of wide field of view (large) goggles, have both been shown to significantly boost VR pain reduction compared to less immersive VR. 15 In addition to reducing the amount of pain reported by participants during brief painful stimuli, studies using functional Magnetic Resonance Imaging (fMRI) have shown large reductions in pain-related brain activity during VR.…”
Section: Research Using Wide Field Of View Vr Goggles and Interactivementioning
confidence: 99%
“…Virtual reality immersion has been shown to be somewhat more effective than audio visual distraction because it augments detachment from viewing and hearing what is happening in the environment [25] [15,[26][27]. In this study it was found that it was significantly easier to carry out the procedure using active video game distraction than passive video viewing of cartoons.…”
Section: Discussionmentioning
confidence: 64%